Motivations for agile adoption among software starups in Saudi Arabia - Al-Sakkaf, Abdullah; Mkpojiogu, Emmanuel O.C.; Hashim, Nor Laily; Omar, Mazni (2017)
Purpose - Agile software development methodology (ASDM) has become a more popular development method for software development, especially for startup companies.Agile adoption is a complex task that dependent on several factors where they are often tailored to be integrated into existing processes (Rohunen et al., 2010).Not all agile processes and practices are suitable for small-scale startups, for instance, there are some practices could have negative impact.The failure of some startups is mainly caused by the failure to develop products due to the lack of adopting of proper development methodology (Giardino et al., 2014). However, there is a lack of studies on factors that affect the selection or adoption of agile methodologies (Tripp & Armstrong, 2014). Furthermore, there is a clear gap in studies that focus in the region (Dingsøyr et al., 2012). Moreover, most of the recent studies do not focus on startups as a medium that adopt ASDM, that currently plays a huge role software industry in the region. There is also a global absence of studies related to startups software development. These gaps provide a good rationale for this study.This study therefore attempts to showcase the motivation rationale for agile adoption among software startups in Kingdom of Saudi Arabia (KSA).